Blade Sharpness and its Effect on the Testing of Body Armours - Watson, Celia H.; Horsfall, Ian; Champion, Stephen M.; Harrod, I. C. (Cranfield University, 2002)
Factors such as edge sharpness and tip sharpness have been identified by Horsfall,1 as keyvariables in the testing of stab and slash resistant armours. This paper evaluates the influenceof blade sharpness on the mechanics of penetration and its relationship with a variety ofmaterials used for body armour systems. The differences in performance between blunt andsharp blades are compared by dynamic tests using an instrumented drop tower, measuringpeak loads and energy to penetration. Variance in the initial impact forces required topenetrate body armour between blunt and sharp blades is shown. However, the total energyto penetration for both sharp and blunt knives was found to be similar for a specific bodyarmour system. Dynamic tests were also used to evaluate the effect of wear on bladeperformance by the comparison of the initial loads for puncture and depth of penetration onaramid and metallic armour systems. The effect of sharpness on the reproducibility of testresults is also investigated and discussed. Various test methods are described for themeasurement of sharpness for both stab and slash and compared. The recent development ofa new non-destructive proof test method to measure tip and edge sharpness is also described.